Antihypertensive, Anti-Inflammatory, and Antiangiogenic In Silico Activity of Lactoferrin-Derived Peptides of Equine Milk Hydrolysate - Meiramkul Narmuratova; Dmitriy Berillo; Zhanar Narmuratova; Pavel Tarlykov; Assiya Serikbayeva; Shattyk Kanayat (Biomedicines)
Background: Equine milk, including its whey proteins, is a source of nutrients and functional components in the human diet, and is especially beneficial for people with weakened immune systems, newborns, and athletes. Objectives Whey proteins in equine milk constitute approximately 20% of the total protein content and include various fractions such as albumin, globulin, and lactoferrin. Lactoferrin is one of the most extensively studied whey proteins in equine milk. Methods: HPLC-Mass analysis, enzymatic hydrolysis, modeling of 3D structure and biological activity in silico. Results: It has antioxidant, anti-inflammatory, and immunomodulatory properties, making it a promising candidate for influencing the various aspects of cardiovascular disease pathogenesis. The products of Lactoferrin hydrolysis by trypsin were confirmed using HPLC. The half-lives of the hydrolysate in the bloodstream and in an intestine-like environment were predicted in silico. Various biological activities (antihypertensive, anti-inflammatory, and antiangiogenic) were also estimated in silico and compared with the corresponding activities of lactoferrin hydrolysate amino acid sequences from camel and dromedary milk. Conclusions: The three-dimensional modeling of lactoferrin hydrolysate peptides was performed to support the development of computational models or simulations, as well as to investigate their potential antimicrobial, anti-inflammatory, or immune-modulating functions in clinical or nutritional applications.